Association of bone turnover C-terminal telopeptide levels, 25-hydroxyvitamin D concentrations and calcium intake in Malaysian adolescents - Majid, Hazreen Abdul; Mustapa Kamal Basha, Muzaitul Akma; Bragt, Marjolijn C. E.; van den Heuve, Ellen G. H. M.; Jalaludin, Muhammad Yazid (Frontiers in Nutrition, 2025)
IntroductionThe C-terminal telopeptide (CTX), vitamin D, and calcium intake are key factors in bone health research. This study aimed to investigate these associations among adolescents.MethodsA cross-sectional study was conducted involving 1,234 students (15-year-olds) from public schools in Selangor, Perak, and Kuala Lumpur, Malaysia. The levels of CTX, 25-hydroxyvitamin D (25(OH)D), and several biomarkers were measured. The seven-day diet history was applied to the habitual dietary intake of the participants.ResultsA generalized linear model was used to quantify the relationship between 25(OH)D concentrations and calcium intake with CTX levels. The results showed that the CTX log concentration was higher in females than males (mean±SD; 1.32±0.47 ng/mL vs. 1.24±0.44 ng/mL). Regarding vitamin D, the percentage of participants with 25(OH)D concentrations below 50 nmol/L was higher among females than males (91.9% vs. 45.4%). In terms of calcium intake, all participants consumed less than 50% (indicating low calcium intake) of the recommended amount, with intakes ranging from 282.0 mg/day to 543.1 mg/day. No significant association was found between 25(OH)D levels below 50 nmol/L and CTX concentrations (p-value > 0.1), but there was a significant association between CTX levels and calcium intake status (β=0.161, p-value < 0.01).ConclusionThis study suggests that higher bone turnover, indicated by elevated CTX levels, is associated with low calcium intake but not with low 25(OH)D levels.